Embracing Aporia: Food sovereignty and how to navigate ethics. Issue 7 (October 2019) - Gordon, Rhyall
A significant section of the alternative food initiative (AFI) literature has expressed concerns about the predisposition of some research to assume neoliberal outcomes from particular AFI practices. As a counterpoint to this, there has been a call for analysis tools that will allow for a more nuanced understanding of the complexities and contradictions of AFI practices. In this paper, I explore the ethical dimension of AFI practices. By interrogating the relationship and interplay between ethics and their correlative ethical practices, new learning and knowledge are generated in both a lay and an academic context. Drawing on Derrida's concept of aporetic ethics, I argue that what allows for such learning to happen is a non-foundational understanding of ethics and ethical practices. When we consider ethics, ethical practices and the relationship between the two as dynamic, fluid and emergent, we develop a disposition that foregrounds reflexivity and learning as key components for 'eating in the anthropocene' . With such a disposition and the learning it generates, researchers, both lay and academic, are in a stronger position to understand the complexities of AFI practices. I offer an illustration of such non-foundational ethics through research on food sovereignty collectives in northern Spain. The collectives demonstrate an understanding of the non-foundational nature of ethics and they employ practices to manage the productive discomfort that comes from destabilising ethics, contesting decisions, reflecting on approaches and using ethics as a process to learn how to care for others.